PENGARUH CURRENT RATIO (CR), RETURN ON ASSET (ROA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2019-2022 - Ningsi, Zahara Surya; Akila, Akila; Mursalin, Mursalin (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to examine the effect of Current Ratio (CR), Return On Asset (ROA), and Debt to Equity Ratio (DER) on Financial distress in transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. Sampling was carried out using the purposive sampling method and then a sample of 15 companies was obtained with sample data from 60 companies financial reports for 4 years of observation. The analysis technique used is the logistic regression analysis technique using SPSS 26. The result of this study concludes that simultaneously Current Ratio (CR), Return On Asset (ROA), and Debt to Equity Ratio (DER) have a significant effect on Financial distress. Partially only the Current Ratio (CR) significantly impacts Financial distress. Return On Asset (ROA) and Debt to Equity Ratio (DER) have no significant effect on Financial distress. Keywords: Current Ratio (CR); Return On Asset (ROA); Debt to Equity Ratio (DER); Financial Distress